2018
DOI: 10.1093/abbs/gmy055
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in red blood cell adaptation to hypoxia

Abstract: Nitric oxide (NO) appears to be involved in virtually every aspect of cardiovascular biology. Most attention has been focused on the role of endothelial-derived NO in basal blood flow regulation by relaxing vascular smooth muscle; however, it is now known that NO derived from red blood cells (RBCs) plays a fundamental role in vascular homeostasis by enhancing oxygen (O2) release at the cellular and physiological level. Hypoxia is an often seen problem in diverse conditions; systemic adaptations to hypoxia perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 155 publications
0
24
0
1
Order By: Relevance
“…Moreover, cells may be less sensitive to on-off changes than plasma/serum samples, reducing false positive/negative results [ 37 ]. Furthermore, metabolomics profiling of RBCs can improve the study on the effect of hypoxia in T2D since these cell act as oxygen delivering systems [ 38 , 39 , 40 ]. Finally, RBCs represent approximately the 70% of the total cell body counting [ 41 ], thus it is important to know more about how their metabolism is affected by T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cells may be less sensitive to on-off changes than plasma/serum samples, reducing false positive/negative results [ 37 ]. Furthermore, metabolomics profiling of RBCs can improve the study on the effect of hypoxia in T2D since these cell act as oxygen delivering systems [ 38 , 39 , 40 ]. Finally, RBCs represent approximately the 70% of the total cell body counting [ 41 ], thus it is important to know more about how their metabolism is affected by T2D.…”
Section: Introductionmentioning
confidence: 99%
“…Less deformable erythrocytes subpopulation is easy to suffer the mechanical stress in microvascular perfusion, which in turn elevates [Ca 2+ ] i leading to further impairment of deformability [59,60]. Therefore, it is not surprising that impairment of deformability is proportional to HbA1c [49,61], because HbA1c reduces the availability of NO, which regulates the cellular deformability [62,63].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…It has been suggested that there should be a unique mechanism for controlling the resistance of pulmonary vessels, according to which the ATP release from the erythrocytes occurs in response to their mechanical deformation, causing stimulation of the synthesis of a NO vasodilator [33].…”
Section: Group III Resistant Ah N=24mentioning
confidence: 99%